New populations of the black-flanked rock-wallaby (Petrogale lateralis) from the Little Sandy Desert and Murchison, Western Australia - Turpin, J.; White, Nicole; Dunlop, J.; Bamford, M. (CSIRO Publishing, 2018)
During two independent fauna surveys, rock-wallaby (Petrogale) scats were recorded from caves located outside the current known Petrogale distribution. Scats collected from Desert Queen Baths (Little Sandy Desert, Western Australia, 2012), and the Barr Smith Range (Murchison, Western Australia, 2015) were genetically analysed and a follow-up motion camera survey confirmed an extant rock-wallaby population at Desert Queen Baths. The combination of sampling techniques overcame the detection difficulties associated with rare and cryptic taxa, and together were important in establishing the presence of Petrogale lateralis from regions where the species has been poorly documented. At both locations, P. lateralis scats were recorded from deep caves situated close to permanent water, reflecting the species' physiological constraints in the arid zone. These records represent significant range extensions of a highly threatened macropod.